2019
DOI: 10.29226/tr1001.2020.168
|View full text |Cite
|
Sign up to set email alerts
|

Income Diversification and Performance: Should banks trade

Abstract: Unprecedented growth in financial innovations, changing customers' expectations, competition from nonbanking entities and regulatory pressure have distorted interest income stream. Thus, banks are now searching for new ways of income generation to cushion themselves against dwindling interest income and as a survival strategy. Proponents of portfolio theory conjecture that income diversification reduces income volatility and increase the profitability. It's from this background the study sought to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
1
1
1
Order By: Relevance
“…With respect to the main coefficients of the model (4), coefficient 𝛽 1 is negative but statistically insignificant at (-0.011), which deduces that the increase in revenue diversification causes a decrease in banks' performance but this effect is statistically insignificant. This result is different with the study of Nisar et al (2018), Githaiga and Yegon (2019), and Addai et al (2022) which demonstrated a positive significant impact of revenue diversification on banks' performance. Nonetheless, this result is agreed with the study of Ngoc Nguyen (2019) and Antao and Karnik (2022) which revealed that revenue diversification negatively affected banks' performance.…”
Section: The Impact Of Business Diversification On Banks' Performancecontrasting
confidence: 99%
“…With respect to the main coefficients of the model (4), coefficient 𝛽 1 is negative but statistically insignificant at (-0.011), which deduces that the increase in revenue diversification causes a decrease in banks' performance but this effect is statistically insignificant. This result is different with the study of Nisar et al (2018), Githaiga and Yegon (2019), and Addai et al (2022) which demonstrated a positive significant impact of revenue diversification on banks' performance. Nonetheless, this result is agreed with the study of Ngoc Nguyen (2019) and Antao and Karnik (2022) which revealed that revenue diversification negatively affected banks' performance.…”
Section: The Impact Of Business Diversification On Banks' Performancecontrasting
confidence: 99%
“…Applying 310 yearly observations from a total sample size of 31 Kenyan commercial banks using panel data for the period of 2008-2017 Githaiga (2020) found a significantly positive relationship impact on income diversification and market power with bank performance. Using a sample size of 31 commercial banks and panel data for the period 2008-2017; Githaiga et al (2019) found the positive significant of income diversification on financial performance. The French 412 financial institutions over 10 years ' (2002-2012) effect of income diversification on profitability is seen as significantly positive (Jouida, 2018).…”
Section: Examine 22mentioning
confidence: 98%
“…Kegiatan bank yaitu menghimpun dana (funding) dan menyalurkan dana (lending) melalui pemberian pinjaman, serta memberikan jasa-jasa bank lainnya (Putra dan Sarawasti, 2020). Beberapa tahun terakhir, industri perbankan mengalami tantangan yang besar yaitu pendapatan bunga yang tidak stabil (Githaiga et al, 2019). Tren penurunan suku bunga menyebabkan penurunan margin bunga bersih perbankan.…”
Section: Pendahuluanunclassified